Current and Future Applications of Reverberation-Mapped Quasars in Cosmology - Panda, Swayamtrupta; Martínez-Aldama, Mary Loli; Zajaček, Michal (Frontiers in Astronomy and Space Sciences, 2019)
Reverberation mapping technique (RM) is an important milestone that has elevated our understanding of Active Galactic Nuclei (AGN) demographics, giving information about the kinematics and the structure of the Broad Line Region (BLR). It is based on the time-delay response between the continuum and the emission line. The time delay is directly related to the size of the BLR which in turn is related to the continuum luminosity of the source, producing the well-known Radius-Luminosity (RL) relation. The majority of the sources with RM data have been monitored for their H$β$ emission line in low redshift sources ($z<0.1$), while there are some attempts using the MgII line for higher redshift ranges. In this work, we present a recent MgII monitoring for the quasar CTS C30.10 ($z=0.90$) observed with the 10-meter Southern African Large Telescope (SALT), for which the RL scaling based on MgII holds within measurement and time-delay uncertainties. One of the most important advantages of reverberation mapping technique is the independent determination to the distant source, and considering the large range of redshifts and luminosities found in AGNs their use in cosmological studies is promising. However, recently it has been found that highly accreting sources show the time delays shorter than expected from the RL relation. We have proposed a correction for this effect using a sample of 117 H$β$ reverberating-mapped AGN with $0.02<z<0.9$, which recovers the low scatter along with the relation. We are able to determine the cosmological constants, $Ω_m$ and $Ω_Λ$. Despite the applied correction, the scatter is still large for being effective for cosmological applications. In the near future, Large Synoptic Survey Telescope (LSST) will cover over 10 million quasars in six photometric bands during its 10-year run. We present the first step in modelling of light curves for H$β$ and MgII and discuss the quasar selection in the context of photometric reverberation mapping with LSST. With the onset of the LSST era, we expect a huge rise in the overall quasar counts and redshift range covered ($z\lesssim7.0$), which will provide a better constraint of AGN properties with cosmological purposes.